PREVALENCE AND DETERMINANTS OF OCCUPATIONAL EXPOSURES TO BLOOD AND BODY FLUIDS AMONG HEALTH WORKERS IN TWO TERTIARY HOSPITALS IN NIGERIA - Ogoina, Dimie; Pondei, Keme; Adetunji, Babatunde; Chima, George; Isichei, Christian; Gidado, Sanusi (African Journal of Infectious Diseases (AJID), 2014)
Background: Healthcare associated infections among health workers commonly follow occupational exposures to pathogens infecting blood or body fluids of patients. We evaluated the prevalence and determinants of occupational exposures to blood/body fluids among health workers in two tertiary hospitals in Nigeria. Methods: In a cross section study undertaken in two tertiary hospitals in North-central and South-south Nigeria in 2011, a structured self-administered questionnaire was used to obtain demographic data and occupational exposures to blood/body fluids in the previous year from doctors, nurses and laboratory scientists. Independent predictors of occupational exposures were determined in an unconditional logistic regression model. Results: Out of 290 health workers studied, 75.8%, 44.7%, 32.9%, 33.9% and 84.4% had skin contact with patient’s blood, needle stick injuries, cut by sharps, blood/body fluid splashes to mucous membranes and one or more type of exposures respectively. Ninety one percent, 86%, 71.1%, 87.6%, 81.3%, and 84.4% of house officers, resident doctors, consultant doctors, staff nurses, principal/chief nursing officers and laboratory scientists, respectively had one or more type of exposures in the previous year (P>0.05). Professional group was found to be the only independent predictor of cut by sharps. House officers and nurses had higher and more frequent occupational exposures than other professional groups. Conclusion: Our results suggest high rates of occupational exposures to blood/body fluid among health workers in Nigeria, especially among newly qualified medical doctors and nurses. Health facilities in Nigeria ought to strengthen infection prevention and control practices while targeting high risk health workers such as house officers and nurses.